Social Entrepreneurial Orientation of Non-Governmental Non-Profit Organizations - Shafna, A. M.; Kodithuwakku, K. A. S. S.; Kumar, Shamala (AMC Indian Journal of Entrepreneurship, 2023)
Purpose : Social entrepreneurial orientation (SEO) is the adaptation of entrepreneurship in an organization that enhances the performance and sustainability of organizations. The study assessed the levels of SEO, including its key dimensions (social innovativeness, social proactiveness, social risk-taking, and socialness), across different types of non-governmental non-profit organizations (NPOs) and identified factors that affect SEO. Methodology : One hundred and ten non-governmental organizations in Sri Lanka’s Ampara District were investigated. The owners or management of the organizations provided the information. The study included a structured questionnaire, and Stata 19 was used for the analysis. Findings : Results showed that levels of SEO varied greatly depending on the type of company. SEO was significantly positively correlated with organization size, organic organizational structure, government non-financial support, and strong-tie resource mobilization. NPOs with financial government-supported and revenue-generating operations have much higher SEO. Additionally, the gender and race of the owners or management made a big difference in SEO. Male-owned or managed businesses displayed higher SEO than those with female owners or managers. According to religion, the SEO of NPOs was found to be in the following order: In descending order, the names of business owners or managers who represented Islam, Roman Catholicism/Christianity, Buddhism, and Hinduism are listed. Practical Implications : The study found that more target-oriented support should be provided for the NPOs. These must take into account both organizational and personnel characteristics of organizations. Originality : This study constructed a model to evaluate factors impacting the level of SEO, in contrast to earlier studies on SEO.